INFORMASI DALAM KOLABORASI PERENCANAAN, PERAMALAN, PEMENUHAN PADA RANTAI PASOKAN PERUSAHAAN AGROINDUSTRI - Wiji Utami; Saiful Bukhori; Markus Apriono (UPT Penerbitan Universitas Jember)
Information Systems Collaborative Planning, Forecasting and Compliance (CPFR) is increasingly used to improve supply chain performance. This study uses panel data to examine the learning curve CPFR between PT. Seed Citra Asia, and one of the partners in the field distributors. Identified two key components of CPFR, namely Colaboratif Forecasting (CF) and Colaboratif Replenishment (CR), shows a different learning curve. There is an increased forecasting accuracy immediately after execution CPFR but the rate of increase slowed from time to time, while inventory levels increased initially and begin to decline after a certain period. There are different learning effects in terms of inventory levels when the product is then replaced with a second product. The second product has a lower inventory levels than earlier products.